Conocimiento de los Estudiantes Sobre el Protocolo de Atención Odontológica de Pacientes Oncológicos, Universidad Antonio Nariño, 2022. (2022)
Cancer is a public health problem worldwide, this pathology is created from cells that develop without control and increase beyond normal limits. The treatment for cancer patients is directed by several professionals, among them is the dentist who must be present from the time the disease is diagnosed until the end of the treatment. These professionals must go hand in hand with evidence-based clinical practice guidelines since they are focused on improving the lives of patients. Objective: To identify the knowledge of the students about the dental care protocol for cancer patients, Antonio Nariño University, 2022. Materials and methods: A descriptive cross-sectional investigation was developed, it was carried out in the A semester of the year 2022 with the students from the Faculty of Dentistry of the Antonio Nariño University, Ibagué